KONTRIBUSI KONFORMITAS KELOMPOK TEMAN SEBAYA TERHADAP TENDENSI PERILAKU AGRESI RELASI PADA REMAJA (Studi Korelasional terhadap Peserta Didik Kelas X dan XI SMA Negeri 2 Ngawi Tahun Ajaran 2021/2022) - Nabila Asrafidhia Sudrajat, - (2022)
Research examines the contribution of peer group conformity. Relationship aggression is a form of aggressive behavior that is often overlooked because it is seen as a joke or normal interaction in a friendship. One of the factors that influence the emergence of aggressive behavior in adolescents is the conformity of peer groups, because the peer group as a social environment has an important role in the development of adolescent personality. Teenagers often put the position of peers as a top priority compared to parents or teachers. The research uses a quantitative approach with the correlational method. The study was conducted on students of SMA Negeri 2 Ngawi for the Academic Year 2021/2022 with a sampling technique using the type of saturated sample with a total of 578 students. The data collection technique used the peer group conformity instrument and the relational aggression behavior instrument. Research analysis using non-parametric statistics spearman rho using SPSS 19.0 for windows application. The results showed that there was a significant positive relationship between peer group conformity and relational aggression behavior in adolescents. This means that the higher the conformity of the peer group, the higher the relationship aggression behavior. The peer group conformity variable contributed 20.5% to relational aggression behavior in adolescents. This study recommends personal-social services to reduce relationship aggression behavior in students.